1999
DOI: 10.1006/brln.1999.2120
|View full text |Cite
|
Sign up to set email alerts
|

Discourse Studies in Neurologically Impaired Populations: A Quest for Action

Abstract: the only definitive repository of the content that has been certified and accepted after peer review. Copyright and all rights therein are retained by Academic Press. This material may not be copied or reposted without explicit permission. Discourse studies in neurologically impaired populations:A quest for action AbstractOrganism and environment are in a state of constant interaction, and discourse is viewed as one form of manifestation of this interaction. Through the study of discourse insights can be gain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Brownell & Martino, 1998;McDonald, 1993;Stemmer, 1999). First, the selection of appropriate patient and control groups is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Brownell & Martino, 1998;McDonald, 1993;Stemmer, 1999). First, the selection of appropriate patient and control groups is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…46 Whereas adults with aphasia present with relatively intact gist processing ability and decreased memory for details, individuals with right hemisphere brain damage demonstrate impaired gist-processing ability and relatively intact memory for details. [47][48][49][50] Adults with Alzheimer's disease experience both gist and detail deficits. 51 A recent study with adolescents with moderate to severe TBI identified impaired gist-reasoning despite intact memory for explicitly stated details of texts.…”
Section: Construct Of Gist-reasoningmentioning
confidence: 99%
“…A reviewer insightfully observed that this distinction likely has neurological and/or cognitive correlates, and that this is an arena to which CA is not directly sensitive. How the kinds of analyses that CA generates can be 'married' with current models of brain/mind functioning is an inordinately complex and fascinating issue; and one that researchers working with communication disorders might be uniquely placed to investigate (see Schegloff, 2003a;b). In the context of the present discussion, it is argued that CA's potential contribution will initially take the form of data-driven elaborations of how the conduct of people with RHBD can be viewed in light of various local interactional contingencies.…”
Section: Resultsmentioning
confidence: 99%
“…see Sherratt and Penn, 1990;Myers, 1999;Stemmer, 1999;Lehman Blake, 2005). Although much of this research has focused on narrative and procedural discourse (Kennedy, 2000), a number of researchers have intentionally focused on conversation (e.g.…”
Section: Introductionmentioning
confidence: 99%